On the Way to Mars—Flagellated Algae in Bioregenerative Life Support Systems Under Microgravity Conditions - Häder, Donat‑P. (Frontiers in Plant Science, 2020)
For long-term manned space missions such as a flight to Mars it is not feasible to carry the necessary oxygen, food and water to sustain the astronauts. In addition, the exhaled carbon dioxide needs to be removed from the cabin air. One alternative is to utilize photosynthetic organisms to uptake the CO2 and produce oxygen. In addition to higher plants, algae are perfect candidates for this purpose. They also serve to absorb wastes and clean the water. Cyanobacteria can be utilized as food supplement. Early ground-based systems include MELISSA, CEBAS and the Biomass Production Chamber. The AQUARACK used the unicellular flagellate Euglena which produced the oxygen for fish in a connected compartment. Several closed environmental life support systems (AQUACELLS, OMEGAHAB) have been developed for space experiments on Russian Foton satellites. A later experiment was based on a 60-mL closed aquatic ecosystem launched on the Shenzhou 8 spacecraft containing Chlorella, Euglena and Bulnius in separate chambers. Recently the Eu:CROPIS mission has been launched as part of the DLR compact satellite program. In addition to tomato plants, Euglena is included as oxygen producer. One new approach is to recycle urine on a bacterial filter to produce nitrogen fertilizer to grow vegetables.